2011
DOI: 10.1017/s0212610910000248
|View full text |Cite
|
Sign up to set email alerts
|

¿El empresario nace o se hace? Educación y empresarialidad en la España Contemporánea

Abstract: This article studies the possible effect that education may have upon entrepreneurial success. It uses two data bases, one for Spanish, the other for English entrepreneurs. By means of statistical and econometric analysis, we examine the effects on entrepreneurial behaviour of a series of variables, several relating to education. We compare the Spanish with the English sample. The main conclusions are: education indeed has a considerable bearing upon entrepreneurial success; this bearing is much more evident i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, this link is not clear. For example, there is empirical evidence that there was a connection between university support of entrepreneurship and the entrepreneurial level of activity in Spain and UK in the 20th century (Tortella et al, 2011), while Corduras et al (2008 find evidence of no significant statistical relationship between both variables in present times. A positive effect has been shown between entrepreneurial education and training and the entrepreneurial capacity but as an indirect enabler via cultural and social norms (Diaz-Casero et al, 2011); while a negative effect has been observed between entrepreneurship programs and the intention to become an entrepreneur (Oosterbeek et al, 2010) although students' attitude could be a modulator for a positive relationship (Packham et al 2010).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…However, this link is not clear. For example, there is empirical evidence that there was a connection between university support of entrepreneurship and the entrepreneurial level of activity in Spain and UK in the 20th century (Tortella et al, 2011), while Corduras et al (2008 find evidence of no significant statistical relationship between both variables in present times. A positive effect has been shown between entrepreneurial education and training and the entrepreneurial capacity but as an indirect enabler via cultural and social norms (Diaz-Casero et al, 2011); while a negative effect has been observed between entrepreneurship programs and the intention to become an entrepreneur (Oosterbeek et al, 2010) although students' attitude could be a modulator for a positive relationship (Packham et al 2010).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…This view is solidly supported by large body of empirical evidence (Bates, 1985;Dickson, Solomon, & Weaver, 2008;Tortella, Quiroga, & Moral-Arce, 2011). …”
Section: Personalitymentioning
confidence: 82%
“…Furthermore, entrepreneurs with over the average education are likely to be more successful (Bates, 1985;Davidson & Honig, 2003;Dickson et al, 2008;Tortella et al, 2011). Nevertheless, some of the evidence points towards possible differences across countries, which might be caused by cultural factors (Cowling, 2000).…”
Section: Educationmentioning
confidence: 99%
“…Although the formal educational level of Spanish businessmen did not diverge too much from that of their foreign counterparts (Tortella, Quiroga & Moral-Arce, 2011), formal training of directives was scarce. However, there were exceptions: the IESE had emerged as an important extractive institution for the Spanish management elite and led to the existence of cross advisers between Schools of Business enterprises (Chirosa-Cañavate, Rubio-Mondéjar & Garrués-Ururzun, 2020).…”
Section: The Boom Of Spanish B-schoolsmentioning
confidence: 92%